Sustenabilitatea producţiei şi consumului de bunuri şi servicii - Stanciu, Mariana; Humă, Cristina; Chiriac, Dumitru (Calitatea Vieții, 2011)
Last years trends, particularly in the developed countries, of increasing energy demand, car using and urban garbage disposal, bear an adverse impact on the environment and the quality of life, becoming a high concern for the whole society. Therefore, many international, European and national organizations plead for the implementation of some more sustainable practices of production and consumption. In this direction, the increased utilization of the renewable energy sources, practicing ecological agriculture on larger areas and a smarter urban garbage management are major goals, not only for environmental policies, but also for increasing the quality of life.